Independent Directors, Moving Forward in Exercising Dominant Role: A Case of Malaysian Firms - Michael, Tinggi; Abu Hassan, Md. Isa; Shaharudin, Jakpar; Salawati, Sahari (Sciedu Press, 2014)
Engaging independent directors at the board room is nothing new. The unexpected downfall of Enron and World Com in the 2000 has raised many eyebrows. Tasking internal and external auditors alone seems no longer sufficient to monitor firms’ daily operating processes, procedural and reporting compliance and if not address may deteriorate firms performance. The independent directors’ presence at the board level is increasingly and markedly felt. Many firms continue to move forward in order to make the audience of independent directors more meaningful. The findings from the board structure exploratory content analysis among an estimated panel of 381 Malaysian firms from 2001 to 2009, seems to suggest that increasing majority of independent directors at board room enable them to exercise a more dominant role towards profit orientation.